Making reproducibility a reality by 2035? - Rebecca Taylor-Grant; Matthew Cannon; Allyson Lister; Susanna-Assunta Sansone (International Journal of Digital Curation)
This paper describes a project which identified practical and pragmatic ways to increase the FAIRness and reproducibility of published research. Academic journals have supported Open Science through the implementation of data sharing policies for over ten years; some evidence has since emerged on the additional time, resources and expertise that policy enforcement requires as part of an editorial workflow. A series of publisher workshops facilitated by the EC-funded TIER2 project aimed to identify the key checks needed to enforce strengthened journal data sharing policies and to understand which editorial roles have the capacity to undertake such enforcement. The intended outcome of this work was to establish the workflows and resourcing which can support academic journals to enforce stronger data sharing policies in future.